Heifer feeding and management affect efficiency - Dunham, James R. (Kansas Agricultural Experiment Station, 2011)
Heifer feeding and management programs have a great impact on the efficiency of the future dairy herd. Dairies that feed and manage heifers for calving at about 24 mo of age are optimizing milk production, feed cost for raising heifers, number of replacement heifers available, and return on investment. Replacement heifers represent a considerable investment in labor and feed, with no return on that investment until they freshen. A summary of Kansas DHIA Holstein herds shows that some herds are receiving a good return on investment as early as 22 mo of age, whereas other herds are not reaping any return until 31 mo (Figure 1). The summary also shows that herds with heifers freshening at an average age of 24 to 25 mo have the highest Rolling Herd Averages for milk production.
Keywords: Dairy; Heifer; Feeding; Management